Design and Development of an Internet of Things Based Package Reception Box System - Sitorus, Eva Martina; Suarjaya, I Made Agus Dwi; Bayupati, I Putu Agung (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2023)
Parkage delivery services play a crucial role in facilitating the easy and prompt sending and receiving of goods to the public. The package delivery sector has witnessed significant growth of 33.62% since the outbreak of the Covid-19 pandemic. However, package receipt often presents challenges, including instances of damaged or lost packages. To address these issues, a system for package reception was designed and developed utilizing the Internet of Things (IoT) technology. The system operates by incorporating a UART GM66 Barcode Scanner, ESP-32CAM, Solenoid Door Lock, and Motor Stepper Nema 17. The primary objective of this research is to construct an automated package-reception system that can be controlled securely through a smartphone, thus ensuring protection against theft and package damage. System testing was performed on the functionality of the tool and communication with the telegram bot.